Conditional cash transfers and the double burden of malnutrition among children in Colombia: a quasi-experimental study. Issue 10 (18th March 2016) - Lopez-Arana, Sandra; Avendano, Mauricio; Forde, Ian; van Lenthe, Frank J.; Burdorf, Alex
Abstract: Conditional cash-transfer (CCT) programmes have been shown to improve the nutritional and health status of children from poor families. However, CCT programmes may have unintended and not fully known consequences by increasing the risk of overweight and obesity. We examined the impact of Familias en Acción (FA), a large CCT programme in Colombia, on the double burden of malnutrition among pre-school and school-aged children. Height and weight were measured before programme enrolment and during follow-ups in 1290 children from thirty-one treatment municipalities, being compared with 1584 children from sixty-two matched control municipalities. We used a difference-in-differences approach to evaluate the effect of FA on children's stunting, BMI z -scores, thinness, overweight and obesity, controlling for individual and municipality-level confounders. At baseline, the prevalences of stunting and overweight were 30·3 and 15·4 %, respectively, in treatment municipalities and 27·9 and 17·4 % in control municipalities. FA was associated with reduced odds of thinness (OR 0·26; 95 % CI 0·09, 0·75) and higher BMI-for-age z -scores (BMI z -scores) ( β 0·14; 95 % CI 0·00, 0·27; P <0·05), although the latter was of small clinical significance. The prevalence of stunting, overweight and obesity decreased over time, but the effect of FA on these outcomes was not significant. The CCT programme in Colombia reduced the odds of thinness, but had no effect on stunting, a more prevalent outcome. The FA programme had no effect on overweight or obesity, although BMI z -scores were higher for children under treatment, raising the possibility of an increase of small clinical significance on BMI among pre-school and school-aged children.